Do Frequent Antenatal Care Visits Ensure Access and Adherence to Intermittent Treatment of Malaria in Pregnancy in an Urban Hospital in South West Nigeria? (2013)
The relationship of antenatal clinic (ANC) attendance and factors that could affect intermittent preventive treatment (IPT) uptake among 339 parturient women was examined. Respondents were enrolled over a period of three months in a secondary healthcare facility within 24 hours of delivery. Demographic details, delivery and antenatal history, insecticide treated net (ITN) use, and history of IPTp-Sulfadoxine-Pyrimethamine (SP) use in the index pregnancy were recorded. Finger and heel pricks blood samples from mothers and neonates respectively were used to detect malaria parasitaemia and to determine packed cell volume (PCV). Median number of ANC visits made by the enrollees was 4.0 (IQR=2.0) with a range of 1-20 visits. Two hundred and eleven (62.2%) enrollees made ≥4 ANC visits. Primigravidae [70 (40.7%)] were more likely than multigravidae [67 (38.4%)] to make their first antenatal visits in the second trimester. Eighty-eight (26.0%) received at least one dose of IPT-SP while 17 (5.0%) received the recommended two doses (first dose after the first trimester and a month later). Adherence increased with the number of ANC visits. Adherence was significantly higher among those who had ≥4 ANC visits compared with those who had <4 ANC visits. Directly observed therapy (DOT) was reported in 35.3%. The main reasons given for not taking two doses of SP were: that SP was administered once, 27 (38.1%) and reasons unknown, 14 (19.7%). In this study, there was low IPT-SP uptake and adherence. Adequate supervision of health workers as well as health education of pregnant women is needed to encourage adherence to IPTp-SP.